2021
DOI: 10.29333/ejmste/11375
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Mathematical Modeling Attitude Scale for Malaysian Mathematics Teachers

Abstract: This work sets out to examine the validity and reliability of the Mathematical Modeling Attitude Scale (MMAS), a instrument measuring teachers' attitude towards mathematical modeling. A cross-sectional survey research was utilised to describe the validity and reliability of the MMAS. The population of the present study focused on Malaysian mathematics teacher in primary and secondary schools (N = 171) and this was achieved using convenience sampling. Exploratory factor analysis (EFA), confirmatory factor analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…They can also gather a lot of data at once [39]. Finally, they can examine variable relationships [40].…”
Section: A Research Designmentioning
confidence: 99%
“…They can also gather a lot of data at once [39]. Finally, they can examine variable relationships [40].…”
Section: A Research Designmentioning
confidence: 99%
“…It is on this note that researchers report that such an MM approach concentrates on the algorithmic manipulation, rote learning involving mainly memorization, superficial identification of mathematical meaning and using calculative tools (Karam, 2014;Redish & Kuo, 2015). By contrast, a future MM approach should be realistic in moving from an abstract learning style together with integrating practical learning (Gallegos, 2009;Hidayat et al, 2021). In support of this, it has been suggested that realistic modelling may generate a physical interpretation that justifies the use of mathematical concepts in interpreting the model.…”
Section: Review On the Teaching And Learning Of An Antenna Theory And...mentioning
confidence: 99%
“…They will need to refocus their teaching on the need to pay attention to the meaning of MM and an epistemological model of MM. Among other emphasis, they will also need to focus on the relationship between MM and the teaching of antenna theory and design, the reasoning behind teaching about antennae and their design in line with the physical world, together with a proper understanding of the laws, principles and explanations of physical reality (Gallegoes, 2009;Hidayat et al, 2021).…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…Rasch techniques have been used in the development and validation of several instruments that measure cognitive and affective constructs in science (Sabah et al, 2013;Sondergeld & Johnson, 2014), math education (Hidayat et al, 2021), statistics education (Teman, 2013), and other disciplines (Akour et al, 2021;Al-Thani et al, 2021;Hammouri et al, 2020). However, the Rasch model has not been used previously with SATS-36 data.…”
Section: Purpose Of the Current Studymentioning
confidence: 99%